Women in computer science. The case study of the Computer Science Department of the University of Crete, Greece. (2018) - Papadakis, Stamatios; Tousia, Christina; Polychronaki, Kalliopi
Various international researches lay emphasis on the fact that women are being under represented in the fields of technology, especially in the computer science. A recent investigation in the USA mentions that female participation in information science at academic level decreased from 28% in 2001 to 18% in 2012. Likewise, in the job market of information science, it dramatically shrunk from 36% in 1991 to 25% in 2015. Having considered the above, we wanted to investigate if, at an academic level, the same trend has been correspondingly affirmed in Greece. The analysis of the data relevant to the alumni of the Computer Science Department of the University of Crete, from 1985 since the recent academic year (2016-2017), has been discouraging since it shows a continuous and pejorative under-representation of women in the field of information science.